Development of Chemistry Lecture Sets for Reducing Logical Fallacy in Arguing - Ilham Pradana Putra Harahap; Suyono Suyono; Nuniek Herdyastuti; Sukarmin Sukarmin (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to develop a lecture set designed to reduce the occurrence of logical fallacies by training students' argumentation skills. Method: The lecture sets were developed to refer to the stages of the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Validity was validated by three validators on student activity sheets and argumentative ability assessment sheets. The validity of the test results was obtained based on the mode of calculation and the percentage of agreement between validators. Results: The lecture sets are structured by containing six types of logical fallacies, namely relative privation, blind authority fallacy, hasty generalization, questionable cause fallacy, reification fallacy, and non sequitur, and includes general chemistry lecture material, namely stoichiometry, atomic structure, periodicity of elements, chemical bonds, the concentration of the solution, the equilibrium of ions in the solution, and the colligative properties of the solution. The chemistry lecture sets for reducing logical fallacies in arguing has been declared valid by the validator. Novelty: The results of this study can be used as a reference by teachers, lecturers, or other researchers who wish to study more about logical fallacies.